Low pacemaker incidence with continuous-sutured valves: a retrospective analysis. (June 2017) - Niclauss, Lars; Delay, Dominique; Pfister, Raymond; Colombier, Sebastien; Kirsch, Matthias; Prêtre, René
Background: Permanent pacemaker implantation after surgical aortic valve replacement depends on patient selection and risk factors for conduction disorders. We aimed to identify risk criteria and obtain a selected group comparable to patients assigned to transcatheter aortic valve implantation. Methods: Isolated sutured aortic valve replacements in 994 patients treated from 2007 to 2015 were reviewed. Demographics, hospital stay, preexisting conduction disorders, surgical technique, and etiology in patients with and without permanent pacemaker implantation were compared. Reported outcomes after transcatheter aortic valve implantation were compared with those of a subgroup including only degenerative valve disease and first redo. Results: The incidence of permanent pacemaker implantation was 2.9%. Longer hospital stay ( p = 0.01), preexisting rhythm disorders ( p < 0.001), complex prosthetic endocarditis ( p = 0.01), and complex redo ( p < 0.001) were associated with permanent pacemaker implantation. Although prostheses were sutured with continuous monofilament in the majority of cases (86%), interrupted pledgetted sutures were used more often in the pacemaker group ( p = 0.002). In the subgroup analysis, the incidence of permanent pacemaker implantation was 2%; preexisting rhythm disorders and the suture technique were still major risk factors. Conclusion: Permanent pacemaker implantation depends on etiology, preexisting rhythm disorders, and suture technique, and the 2% incidence compares favorably with the reported 5- to 10-fold higher incidence after transcatheter aortic valve implantation. Cost analysis should take this into account. Often dismissed as minor complication, permanent pacemaker implantation increases the risks of endocarditis, impaired myocardial recovery, and higher mortality if associated with prosthesis regurgitation.